Circular RNA CircNOLC1, Upregulated by NF-KappaB, Promotes the Progression of Prostate Cancer via miR-647/PAQR4 Axis - Chen, Wenbin; Cen, Shengren; Zhou, Xumin; Yang, Taowei; Wu, Kaihui; Zou, Libin; Luo, Junqi; Li, Chuanyin; Lv, Daojun; Mao, Xiangming (Frontiers in Cell and Developmental Biology, 2021)
Background: CircRNAs recently have shown critical roles in tumor biology. However, their roles in prostate cancer (PCa) remains largely unclear. Methods: CircRNA microarrays were performed in immortal prostate cell line RWPE1 and PCa cell lines as DU145, PC3, LNCaP, C4-2 and 22RV1. Combined with upregulated circRNAs in PCa tissues, circNOLC1 expression was validated in PCa cells and tissues via qRT-PCR and FISH. Sanger sequencing, actinomycin D, gDNA and cDNA, RNase R assays were used to assess the circular characteristics of circNOLC1. CCK-8, colony formation, transwell migration assays and mice xenograft models were conducted to evaluate the functions of PCa cells after circNOLC1 knockdown and overexpression. RNA pulldown, luciferase reporter assay, FISH (fluorescence in situ hybridization) and CHIP were utilized to illustrate the further mechanisms of circNOLC1. Results: Our research indicated that circNOLC1 was overexpressed in PCa cells and tissues, and circNOLC1 was more stable than linear NOLC1 mRNA. CircNOLC1 promoted PCa cells proliferation and migration in vitro and vivo. Additionally, we found that circNOLC1 could upregulate PAQR4 expression by sponging miR-647, leading to the activation of PI3K/Akt pathway. Moreover, NF-kappaB was identified to bind to the NOLC1 promoter sites and upregulated both NOLC1 and circNOLC1 expression. Conclusion: CircNOLC1, elevated by transcription factor NF-kappaB, promotes PCa progression via a miR-647/PAQR4 axis, and circNOLC1 is a potential biomarker and target for PCa treatment.